2018
DOI: 10.1002/jcu.22631
|View full text |Cite
|
Sign up to set email alerts
|

Risk of endometrial cancer and endometrial hyperplasia with atypia in asymptomatic postmenopausal women with endometrial thickness ≥11 mm: A systematic review and meta‐analysis

Abstract: Overall the risk for EC/EHA was 2.6 times greater in women with ET ≥11 mm vs women with ET 5-10 mm, although there was significant heterogeneity in estimates across studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…Indeed, the incidence of ET ≥ 4 mm in asymptomatic postmenopausal women have been reported to be up to 17%, extremely high in comparison to the incidence of endometrial cancer (lower than 2/1000) [4,8,11]. In this regard, according to Smith-Bindman et al, we interestingly found a significant risk of cancer only for values of ET considerably higher than 4 mm, starting from 11 mm [14,32]. Intriguingly, the cut-off value 11 mm showed a 100% sensitivity and 80% specificity for EC detection, with a progressive increase of cancer risk for ascending values up to 30 mm.…”
Section: Main Findingssupporting
confidence: 49%
See 1 more Smart Citation
“…Indeed, the incidence of ET ≥ 4 mm in asymptomatic postmenopausal women have been reported to be up to 17%, extremely high in comparison to the incidence of endometrial cancer (lower than 2/1000) [4,8,11]. In this regard, according to Smith-Bindman et al, we interestingly found a significant risk of cancer only for values of ET considerably higher than 4 mm, starting from 11 mm [14,32]. Intriguingly, the cut-off value 11 mm showed a 100% sensitivity and 80% specificity for EC detection, with a progressive increase of cancer risk for ascending values up to 30 mm.…”
Section: Main Findingssupporting
confidence: 49%
“…On the other hand, ACOG stated that TVUS is appropriate for an initial evaluation of postmenopausal bleeding, because an ET of 4 mm or lower seems to have a 99% negative predictive value for EC. We must consider that ET < 4 mm does not exclude all the disease and it remains unclear if an ET cut-off could also be associated with EC in patients without AUB [3,[8][9][10]13,14].…”
Section: Introductionmentioning
confidence: 99%
“…During the 12.5 y (range: 0.3-13.8 y) follow-up period, however, only 14 women developed endometrial carcinoma. More recently, a systematic review found that the risk of endometrial cancer/ endometrial hyperplasia was 2.6 times greater in women with endometrial thickness !11 mm vs women with endometrial thickness 5-10 mm, although there was significant heterogeneity in estimates across studies (Alc azar et al 2018).…”
Section: Clinical Studiesmentioning
confidence: 90%
“…There are many studies showing the cut off of endometrial thickness in asymptomatic postmenopausal women to predict premalignant and malignant lesion-the cut off being 10-11mm. [8][9][10] Asymptomatic postmenopausal women with ET>12mm and positive doppler flow signals are best predictor of malignancy. 11 Postmenopausal women with recurrent bleeding, who are diabetic have higher risk of endometrial malignancy with ET>11mm.In a study by Ulu et al ET of 15 mm and above, risk of malignancy is 3.043 times higher and symptomatic women have higher risk than asymptomatic women.…”
Section: Discussionmentioning
confidence: 99%